Stress Echocardiography-Derived E/e’ Predicts Abnormal Exercise Hemodynamics in Heart Failure With Preserved Ejection Fraction - Chen, Zheng-Wei; Huang, Chen-Yu; Cheng, Jen-Fang; Chen, Ssu-Yuan; Lin, Lian-Yu; Wu, Cho-Kai (Frontiers in Physiology, 2019)
BACKGROUND. The correlation between echocardiographic parameters and haemodynamics data in patients with heart failure with preserved ejection fraction (HFpEF) is unclear. It is important to find a non-invasive echocardiographic parameter for predicting exercise pulmonary capillary wedge pressure (PCWP). AIM. This study sought to determine the correlation between echocardiographic parameters and haemodynamics data at rest and during exercise in HFpEF patients. METHODS AND RESULTS. This study was a cross-sectional cohort exploratory analysis of baseline data from the ILO-HOPE trial. A total of 34 HFpEF patients were enrolled. The average age was 70±12 years, and most (74%) were women. The patients underwent invasive cardiac catheterization and expired gas analysis at rest and during exercise. Echocardiography including tissue Doppler imaging was performed, and global longitudinal strain and other novel diastolic function indexes were analysed at rest and during exercise. At rest, no significant correlation was noted between resting PCWP and echocardiographic parameters. However, a significant correlation was observed between post-exercise PCWP and stress E/e (septal, lateral, and mean) ratio (p=0.003, 0.031, 0.012). Moreover, post-exercise ΔPCWP showed a good correlation with stress E/e (septal, lateral, and mean; all p≤0.001) and global longitudinal strain during exercise (p=0.03). After multivariate regression analysis with adjustment for possible confounding factors including age and sex, there was still a significant correlation between post-exercise ΔPCWP and E/e (r=0.62, p<0.001 for E/emean). CONCLUSIONS. Only stress echocardiography derived tissue Doppler E/e ratio is closely correlated with abnormal exercise haemodynamics (PCWP and post-exercise ΔPCWP) in HFpEF. This echocardiographic marker is substantially more sensitive than other novel echocardiographic parameters during exercise, and may have significant diagnostic utility for ambulatory HFpEF patients with dyspnoea. Clinical trial registration: https://www.clinicaltrials.gov (NCT03620526).